Coupled parity-time symmetric cavities: results from transmission line modelling simulations - Phang, Sendy; Vukovic, Ana; Creagh, Stephen; Sewell, Phillip D.; Gradoni, Gabriele; Benson, Trevor M. (2015)
This paper studies the impact of a dispersive gain/loss material model on Parity-Time (PT) coupled microresonator cavity structures using the time-domain Transmission-Line Modelling method. A modal analysis is also performed to compare the modal composition in the dispersive and non-dispersive cases. Furthermore, a waveguide-to-waveguide coupler based on the coupled PT-resonant microresonators is analysed to see how the resulting modal profiles are manifested in the power transmitted between input/output ports.